Lamotrigine Therapy in Neuronal Lipofuscinosis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1999)
Lamotrigine (LTG) long-term anticonvulsant therapy was evaluated in 29 patients, aged 6-28 years (mean, 14 years), with juvenile neuronal ceroid lipofuscinosis (JNCL), followed for 1-6 years (mean, 3 years) at the Hospital for Children and Adolescents, University of Helsinki, Finland.